Order Runge-Kutta with Extended Formulation for Solving Ordinary Differential Equations - Suryaningrat, Wahyu; Ashgi, Rizky; Purwani, Sri (International Journal of Global Operations Research, 2020)
The mathematical model has been used to understand many phenomena and natural interactions. Since including many variables and parameters, the complex models are not easy to find analytical solutions. In this paper, we analyze one of the family of Runge–Kutta method with an expansion of evaluation function. We applied the proposed method to solve ordinary differential equations problems and compared it with other well-known Runge-Kutta methods. The computation cost and accuracy for each method have been analyzed.